2018
DOI: 10.1007/s40609-018-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Suicide Assessment and Management Among Accident and Emergency Nurses in Kenyatta National Hospital: a Qualitative Study

Abstract: This qualitative study was conducted using key informant interviews with Accident and Emergency and Mental Health staff at Nairobi's Kenyatta National Hospital to examine the current state of suicide assessment and management care at the Department. The interviews probed whether protocols were in place and if the key personnel were aware of these procedures and to what extent evidence-based protocol was used in managing suicidal patients at A&E. We interviewed eight key informants who rotated in the Accident a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 9 publications
2
14
0
5
Order By: Relevance
“…It could also be that if any suicidal symptom was detected using any means, the nurses integrated suicide management practices and referred patient for further management. This is evidenced in a qualitative study done among the same population where if a patient is found to be suicidal, they are referred for counseling [13]. The respondents in this study had a high index of suicide risk suspicion for patients who were raped, between ages 20 and 35 and who have an alcohol problem [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also be that if any suicidal symptom was detected using any means, the nurses integrated suicide management practices and referred patient for further management. This is evidenced in a qualitative study done among the same population where if a patient is found to be suicidal, they are referred for counseling [13]. The respondents in this study had a high index of suicide risk suspicion for patients who were raped, between ages 20 and 35 and who have an alcohol problem [13].…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced in a qualitative study done among the same population where if a patient is found to be suicidal, they are referred for counseling [13]. The respondents in this study had a high index of suicide risk suspicion for patients who were raped, between ages 20 and 35 and who have an alcohol problem [13]. The level of confidence in risk referral process was quite high in this study compared to the other two domains considering there are no formal referral protocols in this particular setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other pointers that nurse or midwife should look out for are voicing feeling trapped, increasing alcohol or drug use, withdrawal from friends, family, and social activities, being anxious or agitated, having sleep disturbances or sleeping all the time, and having dramatic mood or personality changes ( Talseth and Gilje, 2011 ). The nurse or midwife should be vigilant to identify patients at risk of suicide who talk or write about death, dying, or suicide and those who make statements such as “there’s no purpose in life” or “there’s no reason for living” and say goodbye to people as if they will not see them again or gives away cherished belongings ( Kuehn, 2013 ; Maina et al, 2019 ). The nurse or midwife assesses for nonverbal signs that may potentially indicate the patient is considering self-harm, such as avoiding eye contact, tearfulness, crying, or an abrupt change in behavior, such as sudden happiness, which may signal that the patient has solidified the plan to commit suicide ( Maina et al, 2019 ).…”
Section: The Role Of the Nurse In The Care Of Patients With Suicidal Ideationsmentioning
confidence: 99%
“…The nurse or midwife should be vigilant to identify patients at risk of suicide who talk or write about death, dying, or suicide and those who make statements such as “there’s no purpose in life” or “there’s no reason for living” and say goodbye to people as if they will not see them again or gives away cherished belongings ( Kuehn, 2013 ; Maina et al, 2019 ). The nurse or midwife assesses for nonverbal signs that may potentially indicate the patient is considering self-harm, such as avoiding eye contact, tearfulness, crying, or an abrupt change in behavior, such as sudden happiness, which may signal that the patient has solidified the plan to commit suicide ( Maina et al, 2019 ). If any of these signs are identified, it should be reported to the multidisciplinary team including a psychologist for a thorough assessment.…”
Section: The Role Of the Nurse In The Care Of Patients With Suicidal Ideationsmentioning
confidence: 99%